Frontal Convergence and Vertical Velocity Measured by Drifters in the Alboran Sea. Issue 4 (12th April 2021) - Tarry, Daniel R.; Essink, Sebastian; Pascual, Ananda; Ruiz, Simón; Poulain, Pierre‐Marie; Özgökmen, Tamay; Centurioni, Luca R.; Farrar, J. Thomas; Shcherbina, Andrey; Mahadevan, Amala; D'Asaro, Eric
Abstract: Horizontal and vertical motions associated with mesoscale (10–100 km) and submesoscale (1–10 km) features, such as fronts, meanders, eddies, and filaments, play a critical role in redistributing physical and biogeochemical properties in the ocean. This study makes use of a multiplatform data set of 82 drifters, a Lagrangian float, and profile timeseries of temperature and salinity, obtained in a ∼1‐m/s semipermanent frontal jet in the Alboran Sea as part of CALYPSO (Coherent Lagrangian Pathways from the Surface Ocean to Interior). Drifters drogued at ∼1‐m and 15‐m depth capture the mesoscale and submesoscale circulation aligning along the perimeter of fronts due to horizontal shear. Clusters of drifters are used to estimate the kinematic properties, such as vorticity and divergence, of the flow by fitting a bivariate plane to the horizontal drifter velocities. Clusters with submesoscale length scales indicate normalized vorticity ζ / f > 1 with Coriolis frequency f and normalized divergence of δ / f ∼ O (1) occurring in patches along the front, with error variance around 10%. By computing divergence from drifter clusters at two different depths, we estimate minimum vertical velocity of O (−100 m day −1 ) in the upper 10 m of the water column. These results are at least twice as large as previous estimates of vertical velocity in the region. Location, magnitude, and timing of the convergence are consistent with behavior of a Lagrangian float subducting in the center of a drifter cluster. These results improve our understanding of frontal subduction and quantify convergence and vertical velocity using Lagrangian tools. Plain Language Summary: Vertical transport generated by mesoscale and submesoscale flows plays a key role in the exchange of physical and biogeochemical properties between the surface and the ocean interior. Using multiple simultaneous drifter observations, we compute spatial gradients of velocity to obtain estimates of the divergence field. Thanks to the fact that drifters were deployed at two different depths, we can observe the vertical dependence of divergence in the upper 15 m and estimate the associated vertical velocity. In this study, we estimate divergence and vertical velocity in a ∼1‐m/s semipermanent frontal jet in the Alboran Sea by making use of a multiplatform data set including 82 drifters, a Lagrangian float, and along‐shiptrack profile timeseries of temperature and salinity. Key Points: Kinematic properties were calculated from clusters of drifters at the surface (0.5–1 m) and subsurface (15 m) Vertical velocities estimates were obtained from drifter‐calculated divergence A subduction event measured with a neutrally buoyant float was captured and is consistent with patterns of convergence measured from drifters